2008
DOI: 10.1002/nau.20577
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral versus bilateral stage I neuromodulator lead placement for the treatment of refractory voiding dysfunction

Abstract: Bilateral stage I neuromodulation trial provides a significantly higher rate of improvement in refractory voiding symptoms to allow for the progress to stage II implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…[10][11][12] Our success rates in this study fall within the published norms. Several authors have demonstrated that advanced patient age, male gender, increased duration of symptoms and the presence of concomitant medical comorbidities decrease the likelihood of success following SNM.…”
Section: Discussionsupporting
confidence: 85%
“…[10][11][12] Our success rates in this study fall within the published norms. Several authors have demonstrated that advanced patient age, male gender, increased duration of symptoms and the presence of concomitant medical comorbidities decrease the likelihood of success following SNM.…”
Section: Discussionsupporting
confidence: 85%
“…Pham et al placed unilateral stage 1 S3 leads in 55 patients and bilateral leads in 69 patients with refractory voiding dysfunction. Stage I trials were successful in 32/55 (58%) and 53/69 (76%) of unilateral and bilateral cohorts, respectively ( P =0.03), with no statistically significant difference in complications 16. Scheepens et al evaluated unilateral versus bilateral stimulation in patients with chronic voiding dysfunction.…”
Section: Pathophysiology/mechanismmentioning
confidence: 99%
“…Testing can be done with one electrode or with two bilaterally placed electrodes 35. The Pham study reported significantly higher success rates of the PNE test in patients who were evaluated with bilateral electrodes, but these results were not supported by an earlier study by Scheepens et al36,37 After the procedure, the patients are evaluated to objectify how much improvement is in their symptoms with SNS. This is done with voiding diaries and urodynamic investigations (especially in patients with urinary retention).…”
Section: Neuromodulationmentioning
confidence: 98%